ANALISIS EFEKTIVITAS PENERIMAAN PBB-P2 DAN KONTRIBUSINYA TERHADAP PAD PEMERINTAH KABUPATEN PIDIE - Tarmizi Tarmizi; Lilis Maryasih; Teuku Maimun Azhari (KOLEGIAL, 2018)
This study aims to analyze the effectiveness of PBB-P2 acceptance and its contribution to Pidie District PAD for the 2014-2016 fiscal year. This research is a qualitative research, using secondary data sources in the form of Local Government Financial Reports (LKPD). Data analysis techniques were carried out descriptively, using financial ratio calculations to determine the level of effectiveness and contribution of PBB-P2 revenues. The results showed that PBB-P2 receipts in the Pidie District Government were still not effective, because the achievement of an average target was 73.5% per year. Then in terms of its contribution to regional taxes and Pidie District PAD is still very lacking, with PBB-P2 contribution to regional taxes averaging 3.7% per year, and the contribution to PAD on average is 0.3% per year.